Abdominal cocoon syndrome (idiopathic sclerosing encapsulating peritonitis): An extremely rare cause of small bowel obstruction—Two case reports and a review of literature - Alsadery, Humood A.; Busbait, Saleh; AlBlowi, Abdulrahman; Alsawidan, Morshed; AlBisher, Hassan Mohammed; Alshammary, Shadi (Frontiers in Medicine, 2022)
Introduction Sclerosing encapsulating peritonitis (SEP) is a rare cause of intestinal obstruction in which the bowel and internal abdominal organs are wrapped with a fibrocollagenous cocoon-like encapsulating membrane [1,2]. SEP is divided into two entities: abdominal cocoons (AC), also known as idiopathic or primary sclerosing encapsulating peritonitis, which is of extremely rare type, and secondary sclerosing encapsulating peritonitis, which is the more common type. Case presentation Two male patients from India, a 26 year old and a 36 year old, presented to our hospital complaining about abdominal pain associated with nausea and vomiting without any history of previous surgical interventions; the patients' vitals were stable. Preoperative diagnosis of abdominal cocoon was established by abdominal computed tomography. It showed multiple dilated fluid-filled small bowel loops in the center of the abdominal cavity with thin soft tissue, non-enhancing capsules encasing the small bowel loops with mesenteric congestion involving small and large bowel loops. Both patients underwent complete surgical excision of the sac without intraoperative complications. Patients had a smooth postoperative hospital course and were discharged home in good conditions. Conclusion Patients with abdominal cocoons have a non-specific clinical presentation of intestinal obstruction. A high index of clinical suspicion in combination with the appropriate radiological investigation will increase the chance of preoperative detection of the abdominal cocoon. In patients with complete bowel obstruction, complete excision of the peritoneal sac is the standard of care.